Assessment of Cryptosporidium and Helminth Contamination in Vegetables in Kuching, Sarawak - Tunku Syed Izzuddin, Tunku Syed Azhar (Universiti Malaysia Sarawak, 2017)
Vegetables are edible in both raw and cooked depending on vegetable types. It supplies good values of nutrition to human health and yet also can be the main vehicle of transmission for parasites by which can cause gastrointestinal illness. Thirty two vegetable samples taken from 10 different locations were washed in saline solution with physical rub and were let for 24 hours sedimentation. The top solution was discarded and only the bottom sediment was concentrated by centrifugation before the samples were brought to sucrose flotation technique. Modified Zeihl-Neelsen technique and Lugol's iodine solution were applied to Cryptosporidium and helminths detection, respectively. Lastly, the processed samples were observed under a compound microscope for confirmation of morphology, physical size and identification types of parasite. The parasite most encountered was Ascaris ova (29.4%) and followed by Hookworm ova (23.5%), Toxocara ova (11.8%), and Strongyloides ova (5.9%) from the vegetable samples in organic farms and retail markets in Kuching, Sarawak. Ascaris ova, Toxocara ova and hookworm ova were found positive to most ground type of vegetables. Further study are recommended on detection and enumeration of these parasites for future food security and health concerns.